1992
DOI: 10.1089/lps.1992.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic Hernia Through the Foramen of Morgagni: Laparoscopic Repair Case Report

Abstract: Laparoscopic repair of a diaphragmatic hernia through the foramen of Morgagni in a 67-year-old woman with symptoms of partial colon obstruction is described. The patient had a prompt and complete recovery with no evidence of recurrence one year after surgery. The technique, which incorporates the rectus abdominal fascia in the repair, may be suitable for other laparoscopic surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
99
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(108 citation statements)
references
References 3 publications
1
99
0
6
Order By: Relevance
“…The sac is usually not removed; as this may result in massive pneumomediastinum with potential respiratory and circulatory complications. 8 We could find only two case reports of laparoscopic repair of Morgagni hernia on literature review in octogenarian patients. Vinard et al reported an eighty four year old male patient who underwent primary closure of the defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sac is usually not removed; as this may result in massive pneumomediastinum with potential respiratory and circulatory complications. 8 We could find only two case reports of laparoscopic repair of Morgagni hernia on literature review in octogenarian patients. Vinard et al reported an eighty four year old male patient who underwent primary closure of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The first laparoscopic repair was reported by Kuster et al in 1992. 8 Laparoscopy is an excellent way to confirm diagnosis and to repair non-complicated hernia of Morgagni. The hernia sac can be easily viewed through the laparoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of fusion of these structures in the retroxiphoid region results in a Morgagni hernia. [3] Specifically, it arises from a septum transversum defect due to failure of closure of the pars sternalis and the seventh costochondral arch, known as Larrey's space. [4] Diaphragmatic hernia through this space was first described by the Italian anatomist Giovanni Morgagni in 1769.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Acute symptoms may be due to bowel obstruction, but the incidence of this is very low. [2,3] The overwhelming majority of Morgagni hernias are diagnosed in children, though approximately five percent are diagnosed in adults. [1] The most common adult presentation is in middle-aged, overweight women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation